VICTORIA PARK: A DEMOCTRATIC PUBLIC OPEN SPACE FOR INDONESIA DOMESTIC HELPERS (TKW) - Parmonangan Manurung (Diponegoro University, 2011)
Victoria Park is the largest city park in Hong Kong. This city park is not only known in Hong Kong, but also very well known in Indonesia as a gathering place for Indonesia domestic helpers (TKW) in Hong Kong. This research tried to find out some determinant factors that have been affected the public open spac of Victoria Park to be a gathering place for thousands of TKW in Sunday and holidays as their day off. In order to get the results of research, some methodological research had been conducted such as: observation (survey), mapping, interviews and literature studies. The results showed that Victoria Park has a number of factors capable of meeting the needs of domestic help-ers in Hong Kong, these factors consist of internal factors and external factors. Internally, the character and functions held Victoria Park became a very influential factor, while externally, the accessibility and support functions around Victoria Park also has a considerable influence.